(untitled) (Journal of Industrial and Mechanical Engineering, 2020)
The growth of the solar thermal market both globally and in Argentina, has generated an increase in imports and local production of various solar thermal collectors with very heterogeneous characteristics. The extension of the Argentine territory presents a great amplitude of temperature and solar radiation; these are the main variables that affect the performance of solar collectors. This work analyzes the performance of 2 typical solar collectors, flat plate and vacuum tube, for annual mean temperature and radiation values for the months of June and January, determining how the yields of both collectors vary, and then mapping of the Argentine Republic through Geographic Information Systems (GIS) that show how yields vary throughout the territory for the aforementioned conditions.